POLA KERAGAMAN GENETIK PADA PERMUDAAN ALAM CENDANA DI KAWASAN DESA WISATA BEJIHARJO, KARANGMOJO, GUNUNGKIDUL - , FIQRI YUDA ADAM ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Recently sandalwood is categorized as Critically Endangered Species due to degradation and habitat loss in its natural population all over the world. Since 2004, it was stated to be Extinct in the Wild in its natural population in NTT